Measured physical activity in anorexia nervosa: Features and treatment outcome. Issue 7 (25th May 2013) - El Ghoch, Marwan; Calugi, Simona; Pellegrini, Massimo; Milanese, Chiara; Busacchi, Marcello; Battistini, Nino Carlo; Bernabè, Jasmine; Dalle Grave, Riccardo
ABSTRACT Objective To assess the role of measured physical activity (PA) in anorexia nervosa treatment outcome, and to compare the PA of patients with anorexia nervosa with age‐matched controls. Method PA was assessed by means of Sense Wear Armband before and after a cognitive‐behavioral inpatient treatment in 53 consecutive females with anorexia nervosa, and in 53 healthy age‐matched controls. Results At baseline, patients with anorexia nervosa exhibited a higher duration of moderate–vigorous PA (MVPA≥3 Metabolic Equivalent Tasks (METs)) than controls (t = 2.91; p = .004). Dropouts had higher duration (sec) and expenditure (kcal·day−1) of MVPA than completers. At the end of treatment, completers had a higher number of daily steps, MVPA duration, and expenditure than controls. However, PA was not correlated to eating disorder psychopathology either before or after treatment. Discussion PA is higher in patients with anorexia nervosa than age‐matched controls both before and after treatment, and is associated with treatment dropout. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:709–712)